Diseño Técnico de una escombrera de estériles para la Sociedad Minera de Hecho Cordillera del Cóndor, en el área de concesión Nanguipa, código 501410, ubicada en el sector Cerro Colorado, parroquia de Guayzimi, cantón Nangaritza, provincia de Zamora Chinchipe. - Toledo Encalada, Carlos Fernando (2023)
The objective of the current research is to propose a design for the location of a heap for the Sociedad Minera de Hecho Cordillera del Cóndor, in the Nanguipa concession area, code 501410. The location of the heap, was taken into account topographic criteria, storage capacity, area, storage volume, useful life, mine-heap distance and stable socio-environmental parameters. For the modeling of the site, the variables of topography, water network, climate, vegetation, geology and geomechanical properties were taken into consideration. The research consists of the geological, geotechnical and structural characterization of the base of the emplacement site and the sterile rock that is going to be deposited in the heap, the determination of the methodology for the selection of the emplacement, prior to possible emplacement alternatives. To consider the alternatives, a prior recognition of the study area was made to analyze and study the morphology of the terrain, conformation of streams or ravines, topographic characteristics, existence of fall materials, fractures and surface water runoff. In order to provide an alternative solution to the problem of affecting the natural environment due to the poor disposal of sterile material, the design of a dump that meets the technical and stability criteria is proposed. Keywords: Heap sterile, geotechnical geological characterization, place emplacement, technical design.